Torah Overtones in the Epilogues of Qoheleth - Attard, Stefan M. (Verbum Vitae, 2022)
This article focuses on the two epilogues of Qoheleth, namely 12:9–11 and 12:12–14 and is an attempt to unravel the relationship of the words of the sage with Torah, the latter featuring as miṣwōṯ in v. 13. It is often held that these epilogues were written by someone other than the author of the book at large, and that their function (especially that of the second one), is to highlight the importance of the Torah over and against the words of the wise. Such a position is hereby contested and a rereading of these epilogues is offered. Two specific questions are addressed: Are these epilogues, particularly the second one, meant to downplay the words of the wise in relation to Torah? Conversely, how do the images employed, namely those of the goad, the nails, and the shepherd, possibly constitute a subtle reference to the divine commandments given by God himself? An analysis of the structures of the two epilogues and of the concepts used – this being done especially through an intertextual reading – is carried out hand in hand with a careful translation of the most pertinent texts. Moreover, the similarity of salient concepts found in the epilogues to Pentateuchal and Prophetic texts that have a pertinent canonical position is highlighted, thereby bearing light on the conclusion of Qoheleth. Finally, certain rabbinical interpretations are employed to further unpack the meaning of the texts in question. This exercise leads the author to hold that a positive relationship between sapiential wisdom and Torah is made both in the final epilogue, where the commandments are mentioned, and also in the first epilogue.